Constitutional and Legal Rights of Minorities in Iraq and the Kurdistan Region -A Comparative Analytical Study- - Aso Hamashin Abdulkarim Gazalani (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
This study deals extensively with the subject of minorities living in Iraq and the Kurdistan Region. This study has used and benefited from constitutional and legal data to make representation in order to identify the extent to which minorities’ basic rights are proclaimed as a genuinely belonging to the social fabric of Iraq and the Kurdistan Region. And, when comparing between both federal laws and Kurdistan Region; this brief study finds that political, religious and cultural rights are considered to be at the core of the study of the minority groups and their basic issues. Regardless of the differences between them, studying these laws with others and the emphasis put on each of them, political, civil, religious and cultural rights, in accordance with the priority of these minorities, as well as the rights and the most important rights enshrined in the constitutions and laws in their interests. This research is concerned with different aspects of constitutions of other countries populated by national and religious minorities, including America, Iran, and Syria.